The Attachment Function of Acute and Chronic Suicidal Illness in the Psychotherapy of an Adult Female Incest Survivor. - Greenfield, Robert (Clinical Social Work Journal, 2014)
This paper presents the attachment-focused psychotherapy of a suicidal adult woman with a history of paternal incest, paternal suicide, and maternal death; the latter provoked the patient's near lethal overdose. Psychotherapy with this patient posed formidable clinical challenges because killing herself represented the internalization of profound incest-related shame and pathological beliefs about herself and mother that permeated her whole way of being. By focusing on the patient's multiple working models of attachment associated with the incest and father's suicide, I illustrate the intergenerational transmission of unresolved trauma underlying her suicidal illness. The implications for practice emphasize how understanding and utilizing the intersubjective disorganized attachment dynamics facilitated the patient's internalization of more adaptive and life-affirming views of self and surrounding conditions.